1989
DOI: 10.1152/ajpcell.1989.257.2.c365
|View full text |Cite
|
Sign up to set email alerts
|

Simulated ischemia and intracellular pH in isolated ventricular muscle

Abstract: Isolated guinea pig papillary muscles were subjected to an in vitro model of ischemia, consisting of superfusion arrest and immersion in paraffin oil, which results in restriction of substrate supply and metabolite washout. Intracellular pH (pHi) and surface pH (pHs) were measured with glass microelectrodes. Contractile force declined to 82% of the pre-"ischemic" value after 2 min and to 37% of the control value after 10 min. In addition, a shortening of the time to peak and duration of contraction was noted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 38 publications
3
20
0
Order By: Relevance
“…The depolarization in membrane potentials and shortening of APD induced by the present method were in agreement with previous results obtained in the global ischemia for guinea pig (38), porcine (39) and dog heart (40). However, in the present study, intracellular acidification induced by simulated ischemia was greater than that reported by previous authors (32). At this moment, we have no explanation for the discrepancy between the present results and theirs, but the magnitude of intracellular acidification observed in the present study was within the range reported for ischemic myocardium from the normal values of around 7.2 to values as low as 6.3 (41) or even 5.7 (42).…”
Section: Simulated Ischemiasupporting
confidence: 93%
See 3 more Smart Citations
“…The depolarization in membrane potentials and shortening of APD induced by the present method were in agreement with previous results obtained in the global ischemia for guinea pig (38), porcine (39) and dog heart (40). However, in the present study, intracellular acidification induced by simulated ischemia was greater than that reported by previous authors (32). At this moment, we have no explanation for the discrepancy between the present results and theirs, but the magnitude of intracellular acidification observed in the present study was within the range reported for ischemic myocardium from the normal values of around 7.2 to values as low as 6.3 (41) or even 5.7 (42).…”
Section: Simulated Ischemiasupporting
confidence: 93%
“…Furthermore, the present method is suitable for direct microelectrode measurements of cardiac pHl by stable cell impalements. Although simulated ischemia could not bring down muscle surface P02 to anoxic levels, it has been reported that it exerted larger effects on contractility, action potentials and intracellular pH than hypoxic superfusion (32). The depolarization in membrane potentials and shortening of APD induced by the present method were in agreement with previous results obtained in the global ischemia for guinea pig (38), porcine (39) and dog heart (40).…”
Section: Simulated Ischemiasupporting
confidence: 91%
See 2 more Smart Citations
“…4 Interstitial myocardial pH can also be assessed by implanting a small pH electrode in tissue, or by attaching a vacuum-filled Teflon catheter to a mass spectrometer to measure PCO 2 , which correlates with pH. [12][13][14][15] Interstitial myocardial measurements correspond to intracellular myocardial measurements. Brief coronary occlusion reduces interstitial myocardial pH.…”
Section: Discussionmentioning
confidence: 99%